Developing sustainable models of agroforest-landscape in Bogor, Indonesia - NUGRAHA AKBAR NURROCHMAT; HERRY PURNOMO; MUHDIN MUHDIN; JAMES THOMAS ERBAUGH (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Nurrochmat NA, Purnomo H, Muhdin, Erbaugh JT. 2023. Developing sustainable models of agroforest-landscape in Bogor, Indonesia. Biodiversitas 24: 4324-4333. Deforestation continues in Indonesia even though many regulations and precautions have been taken. It most likely happened due to the less economic contribution from the forestry sector, which caused the conversion from forest lands to more profitable land uses. The forest area covers 125 million hectares (66%) of 190 million hectares of country land but contributes only about 0.60% of the Gross Domestic Product (GDP). An agroforestry scheme is promoted to increase the economic value of the forest to increase both the community welfare and the environmental quality. This study indicates that the best agroforestry commodities for social scenarios are durian, ornamental plants, and laying hens, with the highest potential profit of IDR.143,857,559 (USD.9,652)/hectare/month and 9.19 tons/hectare carbon stock. While for the economic scenario is jackfruit, ornamental plants, and laying hens with a potential profit of IDR.146,908,379 (USD.9,789)/hectare/month and 18.66 tons/hectare carbon stock. In comparison, the ecology scenario promotes nutmeg and ornamental plants with a potential profit of IDR 36,814,280 (USD.2,470)/hectare/month, with the highest of 56.12 tons/hectare carbon stock. This study recommends the appropriate land use models for the government to address the conflict of interest between agriculture and forestry in contributing to Indonesia's FoLU (Forestry and other Land Uses) Net Sink in 2030.